ANALYSIS OF WAYS TO INCREASE COMPETITIVENESS UKRAINIAN METALLURGICAL ENTERPRISES ON THE EXAMPLE OF PJSC "ARCELORMITTAL KRYVIY RIH". PART 1. SINTERING AND BLAST FURNACE PRODUCTION - CHUPRYNOV, YEVHEN; KORENKO, MARYNA; KASSIM, DARIA; REKOV, YURIY; LIAKHOVA, IRYNA; MALII, KHRYSTYNA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
It has been demonstrated that, despite significant challenges, the Ukrainian metallurgical industry has the potential for recovery and development. The implementation of modern technologies, the use of domestic raw materials, and the optimization of production processes are key factors for success. The article analyzes the possibilities of modernizing the sinter plant at PJSC ArcelorMittal Kryvyi Rih through the introduction of a two-layer charge with different carbon content and reactivity. Optimal parameters for sintering a two-layer charge with the aforementioned indicators have been established. Studies have shown that the use of fuel with high and low reactivity according to the developed technology allows improving the quality of sinter, reducing specific fuel consumption, and increasing the productivity of the sintering process. The issue of using Ukrainian bentonite clays for the production of pellets has been considered, and the influence of charge moisture content and the type of bentonite used on the physicomechanical properties of pellets has been analyzed. It was found that increasing the moisture content of the charge before pelletizing led to changes in the properties of the obtained pellets, regardless of the type of bentonite used. It has been shown that the use of bentonite clay from the Cherkasy deposit has prospects for implementation in the technological process of pellet production at Ukrainian enterprises. A new type of iron ore raw material for blast furnace smelting has been proposed, combining the advantages of sinter and pellets. The combination of traditional anthracite charging with the use of developed local sinters with a high iron content and residual carbon opens up new possibilities for optimizing the blast furnace process.